In silico screening of genes coding for secondary metabolites in the phytopathogenic fungus Stemphylium lycopersici - Franco, Mario Emilio Ernesto (2016)
Secondary metabolites (SMs) are a highly diverse set of low molecular weight bioactive compounds that play different biological roles. They are dispensable when microorganism are cultivated in vitro, but usually play a key role in nature, providing organisms with adaptive advantages in different niches. Among them, toxins produced by phytopathogenic fungi play crucial roles in virulence and host nutrition. We hypothesized that the genome of Stemphylium lycopersici strain CIDEFI-216, an etiological agent of tomato gray leaf spot, contains several gene clusters that code for the synthesis of SMs, such as those involved in the biosynthesis of virulence factors. We searched by means of the bioinformatic tools Secondary Metabolite Unknown Region Finder (SMURF) and Antibiotics and Secondary Metabolite Analysis Shell (antiSMASH) enabling the ClusterFinder algorithm for potential SMs gene clusters within the draft genome sequence of the fungus. This lead to the prediction of 32, 33 and 64 additional SMs gene clusters by SMURF, antiSMASH and ClusterFinder, respectively. They included polyketides synthase (PKS), non-ribosomal peptide synthase (NRPS), terpene synthase, dimethylallyl tryptophan synthase, hybrid PKS-NRPS, lanthipeptide synthase, fatty acid synthase and others gene clusters of unknown nature. This knowledge provides critical information to understand the biological bases of the tomato-S. lycopersici interaction.